2022
DOI: 10.1080/21655979.2022.2063651
|View full text |Cite
|
Sign up to set email alerts
|

Simple and robust 3D bioprinting of full-thickness human skin tissue

Abstract: Artificial skins have been used as skin substitutes for wound healing in the clinic, and as in vitro models for safety assessment in cosmetic and pharmaceutical industries. The three-dimensional (3D) bioprinting technique provides a promising strategy in the fabrication of artificial skins. Despite the technological advances, many challenges remain to be conquered, such as the complicated preparation conditions for bio-printed skin and the unavailability of stability and robustness of skin bioprinting. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Studies usually culture organotypic skin models up to 3 weeks [ 37 , 38 , 39 , 40 ], but in light of preclinical studies, culture times longer than 3 weeks could be required. In the development of 3D models, predominantly the histology, composition of the extracellular matrix, or cell survival is studied [ 41 , 42 ]. Our study not only showed that the FSEs were capable of forming a functional epidermis, but also showed that these models were able to regenerate after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies usually culture organotypic skin models up to 3 weeks [ 37 , 38 , 39 , 40 ], but in light of preclinical studies, culture times longer than 3 weeks could be required. In the development of 3D models, predominantly the histology, composition of the extracellular matrix, or cell survival is studied [ 41 , 42 ]. Our study not only showed that the FSEs were capable of forming a functional epidermis, but also showed that these models were able to regenerate after thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…As this natural polymer provides a suitable environment for cell growth, inks composed of such material have been employed to design several tissue-like systems or models (tumor, skin, muscle) [112][113][114]. A noteworthy example developed a heterogeneous tumor system based on a composite ink consisting of gelatin, alginate and cellulose.…”
Section: Gelatin As Bioink For 3d Printingmentioning
confidence: 99%
“…The majority of the top layer of the epidermis is composed of keratinocytes organised into the keratinised stratified squamous epithelium [33]. This basement membrane also separates the epidermis from the dermis [62]. In the stratum corneum, proliferative cells undergo differentiation sequentially, with newly undifferentiated cells at the bottom and terminally differentiated cells at the surface [11].…”
Section: Skin Tissue 3d Bioprintingmentioning
confidence: 99%
“…The papillary area is rich in type III collagen, whereas the reticular region has more type I collagen [63]. This variation in the ratio of collagen in the extracellular matrix of the dermis is responsible for the skin's elasticity and mechanical strength [62]. Due to the numerous cell types, it contains, including vasculature, neurons, and hair follicles, the dermis links the rest of the body and the skin [62,63].…”
Section: Skin Tissue 3d Bioprintingmentioning
confidence: 99%